The challenge of mathematical discussions in teachers’ professional practice - Ponte, João Pedro da (2017)
We seek to identify patterns of action in mathematics teachers’ classroom practice regarding class discussions and to determine how these actions provide learning opportunities for students. The study is based on a framework that focuses on two key elements of teaching practice: 1) the tasks that teachers propose to their students and, 2) the way they handle classroom communication. Qualitative methodology is used with data collected from video recordings of a grade 6 class that is studying rational numbers. We conclude that challenging situations usually require teacher preparation and follow-up with supporting/guiding and informing/suggesting actions so that the students can learn what is involved in the teacher’s motivations.